Effect of Dietary Supplemented with Mulberry Leaf Powder on Growth Performance, Serum Metabolites, Antioxidant Property and Intestinal Health of Weaned Piglets - Jiayu Ma; Jian Wang; Xiaoyun Jin; Sujie Liu; Shaofeng Tang; Zhenghua Zhang; Shenfei Long; Xiangshu Piao (Antioxidants, 2023)
Background: The study aimed to explore the effect of mulberry leaf powder (MP) on the performance, serum metabolites and antioxidant property, as well as intestinal health, of weaned piglets. A total of 120 healthy piglets weighing 8.43 ± 1.91 kg (Duroc × (Landrace × Yorkshire); weaned at 28 d) were chosen and classified into four treatments with three replicates of 10 piglets each based on a randomized complete block design (barrow:gilt = 1:1). The diet treatments were a corn–soybean meal basal diet added with 0% (Ctrl), 2% (MP_2), 4% (MP_4) and 6% MP (MP_6), respectively. The feeding experiment was 28 days in total. The feeding period lasted for 28 days in total. Results: The diet supplemented with 2% MP had no detrimental effects on the growth performance, immunity, enzyme capacity and inflammatory factors, as well as intestinal barrier function. MP_2 is capable of decreasing the levels of serum D-lactic acid and lactate dehydrogenase, enhancing the superoxide dismutase capacity in the liver and diminishing the potential pathogenic bacteria Allisonella in the colon. However, compared with MP_2, MP_6 had unfavorable effects on the average daily gain and average daily feed intake; the concentration of serum non-esterified fatty acids; the activities of superoxide dismutase and glutathione peroxidase and the capacity of lipase and amylase, as well as the intestinal barrier function-related mRNA expression of occludin, claudin-1 and mucin-2 in piglets. Conclusion: Taken together, piglets fed with 2% MP had no adverse effect and was capable of improving the serum metabolites, enhancing the antioxidant capacity (SOD) and lowering the potential pathogenic bacteria of the hindgut (Allisonella). However, the highest concentration of MP (6%) may cause detrimental effects for piglets, which are probably associated with the higher antinutritional factors and fiber. Therefore, the dietary supplementation of 2% MP for piglets may be advisable.